Formulasi Sediaan Sabun Padat Ekstrak Etanol Serai Wangi (Cymbopogon nardus L.) - Anida Kurniawati; Andita Eltivitasari; Trilestari Trilestari (Sinteza, 2025)
ABSTRACT Citronella plants (Cymbopogon nardus L) contained active compounds such as citrononeal, citronellol, geraniol. Citronella has been known to have antibacterial, antioxidant and aromatherapy properties. Solid soap is used as a means to cleanse the body and skin from bacteria and protected against exposure to free radicals that have a negative effect on skin health. Solid soap has the benefit of cleaning and brightening the skin, was easy to use and has a relatively affordable price. The research aimed to make solid soap innovations using citronella ethanol extract ingredients. The extraction method used is maceration using 70% ethanol. The preparation of citronella extract solid soap consists of 3 formulas namely FI (2.5%), FII (5%), FIII (7.5%). Physical properties tests carried out on solid soap preparations are organoleptic test, pH test, irritation test, homogeneity test, foam height test, and favourability test. Data analysis in this study was descriptive. Data were obtained from the average observation results of the physical evaluation test, specifically organoleptic test, pH test, irritation test, homogeneity test, foam height test, and favourability test, test in accordance with the requirements of the SNI standards that have been set. The results showed that FI (2.5%), FII (5%) showed that they met the requirements of solid soap preparations such as organoleptic test, homogeneity test, pH test, high foam test, irritation test and favourability test. The difference in concentration in the solid soap formula of citronella ethanol extract had an effect on the physical characteristics of the product. The best formulation of some concentrations of citronella (C. nardus L) ethanol extract solid soap is in formula I with an extract concentration of 2.5%.